Exploring 3D Printing in Drug Development: Assessing the Potential of Advanced Melt Drop Deposition Technology for Solubility Enhancement by Creation of Amorphous Solid Dispersions - Nabil Lamrabet; Florian Hess; Philip Leidig; Andreas Marx; Thomas Kipping (Pharmaceutics)
Background: Melt-based 3D printing technologies are currently extensively evaluated for research purposes as well as for industrial applications. Classical approaches often require intermediates, which can pose a risk to stability and add additional complexity to the process. The Advanced Melt Drop Deposition (AMDD) technology, is a 3D printing process that combines the principles of melt extrusion with pressure-driven ejection, similar to injection molding. This method offers several advantages over traditional melt-based 3D printing techniques, making it particularly suitable for pharmaceutical applications. Objectives: This study evaluates the AMDD printing system for producing solid oral dosage forms, with a primary focus on the thermo-stable polymer polyvinyl alcohol (PVA). The suitability of AMDD technology for creating amorphous solid dispersions (ASDs) is also examined. Finally, the study aims to define the material requirements and limitations of the raw materials used in the process. Methods: The active pharmaceutical ingredients (APIs) indometacin and ketoconazole were used, with PVA 4-88 serving as the carrier polymer. Powders, wet granulates, and pellets were investigated as raw materials and characterized. Dissolution testing and content analyses were performed on the printed dosage forms. Solid-state characterization was conducted using differential scanning calorimetry (DSC) and X-ray diffraction (XRD). Degradation due to thermal and mechanical stress was analyzed using nuclear magnetic resonance spectroscopy (NMR). Results/Conclusions: The results demonstrate that the AMDD 3D printing process is well-suited for producing solid dosage forms. Tablets were successfully printed, meeting mass uniformity standards. Adjusting the infill volume from 30% to 100% effectively controlled the drug release rate of the tablets. Solid-state analysis revealed that the AMDD process can produce amorphous solid dispersions with enhanced solubility compared to their crystalline form. The experiments also demonstrated that powders with a particle size of approximately 200 µm can be directly processed using AMDD technology.